Implikasi Kode Klasifikasi Program Televisi Catatan Si Bocil NET TV Terhadap Tayangan Anak - Siti Anisa Setiani; Hery Supiarza; Salsa Solli Nafsika (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
The classification code applied to television programs is certainly not just a small code that is displayed during the airing process. This code has the meaning to classify programs by age category. The classification code of television programs is intended so that viewers can adjust the viewing to age categories and types of shows that are in accordance with social morals. Catatan Si Bocil Program is a problem to analyze about the process of receiving codes to airing events. Another institution tasked with this classification code is the Film Censorship Board as well as the regulations drafted as a provision of broadcasting guidelines. The purpose of this study is intended to convey how important classification codes are on television programs. The method used is qualitative with a descriptive approach, so that the data used is based on the process of observation, interviews, literature studies and documentation. This study found the process of giving classification codes and impressions that have been given classification codes based on the results of assessments conducted by the Film Censorship Institute. The implications of this research can be a reference for television stations in making programs.